Lo que se baila en Costa Rica: Bolero: análisis musical de una cumbia costarricense - Chaves, Bary (2013)
The present article is part of a group of essays which deal with some manifestations of Latin American music. This particular essay is a research of the rhythm called “cumbia”, and studies a Costa Rican piece in the genre. Following a general overview of cumbia throughout Latin American and Costa Rican history, this article offers the musical analysis of a Costa Rican cumbia, giving as well notated examples and their instrumentation, in order to display a broader study on the subject.